2019
DOI: 10.3390/ijms20051038
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Effect of Silver Nanoparticles on the Tumor Necrosis Factor α-Induced DNA Damage Response

Abstract: Silver nanoparticles (AgNPs) are widely used in many consumer products due to their anti-inflammatory properties. Therefore, the effect of exposure to AgNPs should be investigated in diseased states in addition to healthy ones. Tumor necrosis factor-α (TNFα) is a major cytokine that is highly expressed in many diseased conditions, such as inflammatory diseases, sepsis, and cancer. We investigated the effects of two different sizes of AgNPs on the TNFα-induced DNA damage response. Cells were exposed to 10 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The latter can be distinguished in clathrin-dependent endocytosis, caveolae-dependent endocytosis, macropinocytosis, The ATP assay showed very high versatility and ease-to-use in fact it is used for several different types of nanoparticles like high-density lipoprotein, gold, silver and silica. Furthermore, the use of luminescence as ATP quantification method doesn't show interference with fluorescence/adsorption of nanoparticles Vetten et al, 2013;Cao et al, 2017;Suganuma et al, 2017;Fehaid and Taniguchi, 2019;Silvestri et al, 2019;Wang et al, 2019 Evaluation of NAD + /NADH ratio Luminescence, colorimetry, fluorescence…”
Section: Uptakementioning
confidence: 99%
“…The latter can be distinguished in clathrin-dependent endocytosis, caveolae-dependent endocytosis, macropinocytosis, The ATP assay showed very high versatility and ease-to-use in fact it is used for several different types of nanoparticles like high-density lipoprotein, gold, silver and silica. Furthermore, the use of luminescence as ATP quantification method doesn't show interference with fluorescence/adsorption of nanoparticles Vetten et al, 2013;Cao et al, 2017;Suganuma et al, 2017;Fehaid and Taniguchi, 2019;Silvestri et al, 2019;Wang et al, 2019 Evaluation of NAD + /NADH ratio Luminescence, colorimetry, fluorescence…”
Section: Uptakementioning
confidence: 99%
“…TNF-α induces the upregulation of inflammatory cytokines and causes DNA damage (Fehaid and Taniguchi, 2019;Kay et al, 2019;Shao et al, 2019). These changes result in double-stranded DNA (dsDNA) increases in the cytoplasm of cells, which comprise a phenotype-the senescence-associated secretory phenotype (SASP)-that involves cell senescence and abnormal inflammatory factor infiltration (Choubey and Panchanathan, 2016;Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polystyrene NPs induced aggregation of epidermal growth factor receptors (EGFRs) in A431 cells [23]. In addition, we showed that 200 nm silver NPs reduced lung epithelial cell surface expression of tumor necrosis factor receptor 1 (TNFR1) with increased localization of receptors in the cell cytoplasm [24]. These results suggested that NPs affect cell surface protein localization and expression.…”
Section: Discussionmentioning
confidence: 99%